Vanishing roots - Chong, Brian Zhen Yu (Nanyang Technological University, 2022)
“Vanishing Roots” is an experiential tour design system that addresses the need for heritage education to start young, how it brings out the best in children and deepens classroom learning. The system aims to connect young students to the intangible cultural heritage of Chinatown by bringing them out of the classroom and into a heritage setting for a more immersive and deeper learning.